Озброєння та військова справа населення сіверськодонецького Лісостепу у кінці VІ—IV ст. до н. е. - Гречко, Д. С. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryD. Grechko. Armament and military science of the population who lived in forest-steppe area at the Severskij Donets River at the end of VI—IV centuries BCThe most numerous category of artefacts among sepulchral equipment of Scythian barrows at the Severskij Donets River is armament that was found in 54 % of barrows (the end of VI—IV BC). The armament that has obtained to date coincides with the artefacts from synchronous forest-steppe monuments. This fact confirms the thesis about high degree of material culture unification of residential population in V—IV BC. It does not permit now to choose local peculiarities of the Severskij Donets soldiers' armament at this time.During the end of V—IV BC the contingents of local military units consisted of infantry mainly (85 %) and cavalry (15 %). Excavation of fortification system attests sufficient quality of fortification art that the population had.Thus effective military system allowed the population of Severskij Donets forest-steppe to assert the independence and to be in parity with the neighbours.